Organizational stress and well-being in competitive sport: a systematic review - Simpson, R. A. C.; Didymus, F. F.; Williams, T. L. (International Review of Sport and Exercise Psychology, 2024)
Research on organizational stress in sport has expanded within recent decades. Despite voluminous literature, no systematic reviews exist to congregate findings in a single, rigorous point of reference. Filling this void helps researchers and practitioners to understand organizational stress and its implications for health, well-being, and performance. The objectives of this study were to search for, appraise, and critically synthesize the literature on organizational stress (i.e. stressors, appraisals, coping, emotions) and or well-being within the context of organizational stress in competitive sport, with the intention of progressing conceptual, methodological, and applied understanding. A systematic review was conducted using PRISMA guidelines and robust searches of PsycArticles, PsycInfo, and SPORTDiscus databases. The final sample comprised 55 methodologically sound studies with athletes, coaches, and or support staff. Findings revealed a myriad of organizational stressors, underpinned by a range of situational properties, and managed using various coping options (e.g. problem solving). Appraisals, emotions, and well-being received scant attention in the context of organizational stress. Experiences of organizational stress among athletes, coaches, and support staff have highlighted implications for health - and performance-related outcomes. Future research should consider longitudinal, diary, integrative designs, and analytical pluralism within under-represented populations (e.g. coaches, support staff) to deepen our understanding.